C‐reactive protein, obesity, and the risk of arterial and venous thrombosis. (22nd June 2016) - Horvei, L. D.; Grimnes, G.; Hindberg, K.; Mathiesen, E. B.; Njølstad, I.; Wilsgaard, T.; Brox, J.; Brækkan, S. K.; Hansen, J.‐B.
Abstract : Essentials We performed repeated measurements of C‐reactive protein (CRP) and obesity in a cohort study. CRP was associated with risk of myocardial infarction and venous thromboembolism. CRP was a mediator for risk of myocardial infarction in obese men and women. CRP was a partial mediator for risk of venous thromboembolism in obese women, but not in men. Summary: Background: Low‐grade inflammation in obesity may be a shared pathway for the risk of venous thromboembolism (VTE) and myocardial infarction (MI). Objectives: To investigate the associations between repeated measurements of C‐reactive protein (CRP) and the risks of MI and VTE, and to explore whether CRP mediated these risks in obese subjects. Methods: CRP and obesity measures were collected from 15 134 subjects who participated in one or more surveys of the Tromsø study in 1994–1995, 2001–2002, or 2007–2008. Incident VTEs and MIs were registered until 1 January 2011. Time‐varying Cox regression models were used to calculate hazard ratios of MI and VTE according to categories of CRP and obesity measures. Results: There were 291 VTEs and 920 MIs during follow‐up. High levels of CRP (≥ 3 mg L −1 versus < 1 mg L −1 ) were associated with increased risks of MI (hazard ratio [HR] 1.73; 95% confidence interval [CI] 1.32–2.26) and VTE (HR 1.84; 95% CI 1.22–2.78) in women, but only with MI in men (HR 1.93; 95% CI 1.53–2.44). All obesity measures showed stronger associations with CRP in women than in men. In obese women (body mass index [BMI] of ≥ 30 kg m −2 versus < 25 kg m −2 ), adjustment for CRP attenuated the risk estimate for VTE by 22%, whereas the incidence rates of VTE increased with combined categories of higher BMI and CRP. No association was found in men. Conclusions: Our findings suggest that low‐grade inflammation, assessed by measurement of CRP, is associated with the risks of MI and VTE, and may be a shared pathway for MI and VTE in obesity.